2017
DOI: 10.19082/3598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sexual Counseling on Marital Satisfaction of Pregnant Women Referring to Health Centers in Malayer (Iran): An educational randomized experimental study

Abstract: IntroductionOne of the most important factors in marital satisfaction is the satisfaction of a healthy sexual relationship between spouses. During pregnancy marital satisfaction may decrease due to sexual problems. Sexual counseling to pregnant women may reduce the complications of these problems at this time. This study aimed to investigate the effects of sexual counseling on marital satisfaction of pregnant women. This article is sponsored by the Hamadan University of Medical Sciences.MethodsThis educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…Masoumi also believes that by providing appropriate counselling on sexual issues, the problems in couples' sexual relations are gradually eliminated, and their unawareness turns into perfect knowledge. Moreover, Masoumi et al examined the effect of sexual therapy on marital satisfaction in pregnant women in 2016; they indicated that counselling increased the score for sexual satisfaction, which is consistent with the present study [27]. In 2017 Parhizgar et al concluded that sex education or marital counselling plays an important role in family health, reduces sexual violence in the family, prevents sexually transmitted diseases, develops positive attitudes towards sexual relations and sexual pleasure, reduces family incompatibility, helps gain sexual satisfaction experience and results in couples' sexual satisfaction as a result of couples' marital satisfaction [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Masoumi also believes that by providing appropriate counselling on sexual issues, the problems in couples' sexual relations are gradually eliminated, and their unawareness turns into perfect knowledge. Moreover, Masoumi et al examined the effect of sexual therapy on marital satisfaction in pregnant women in 2016; they indicated that counselling increased the score for sexual satisfaction, which is consistent with the present study [27]. In 2017 Parhizgar et al concluded that sex education or marital counselling plays an important role in family health, reduces sexual violence in the family, prevents sexually transmitted diseases, develops positive attitudes towards sexual relations and sexual pleasure, reduces family incompatibility, helps gain sexual satisfaction experience and results in couples' sexual satisfaction as a result of couples' marital satisfaction [28].…”
Section: Discussionsupporting
confidence: 91%
“…Another study hypothesis suggests that midwife counselling improves sexual satisfaction in women with a low libido [35,36]. The results of the current study indicate the success of the intervention in this regard, which is in line with the study of Masoumi et al as regards the effectiveness of counselling by midwifery personnel [27].…”
Section: Discussionsupporting
confidence: 90%
“…Masoumi et al, in their study, concluded that sexual education or marital counselling promoted family health, reduced sexual violence in the family, prevented sexually transmitted diseases and provided a positive attitude toward sexual relations, sexual pleasure, reduced family inequity and sexual satisfaction. As a result, marital satisfaction is attained by couples [23]. Alidost et al, in their study, demonstrated that after sexual counselling, the mean score of sexual satisfaction in the posttest and the 6-month follow-up was significantly higher than that of the pre-test score [9].…”
Section: Discussionmentioning
confidence: 94%
“…The SSEP protocol was administered for couple counseling in the presence of the couples who were blind of the presence of other couples in the research group. SSE-CP meeting protocol was designed based on similar interventions extracted from textbooks and articles (16,17).…”
Section: Methods Of Studymentioning
confidence: 99%